Establishing a pattern between the mass of the plunger and the translational motion maximum frequency of the working body of the electromagnetic action differential pump - Korobko, Bogdan; Kivshyk, Anton (Academic journal Industrial Machine Building Civil Engineering, 2022)
The article deals with the frequency of translational movement of the working body. The frequency is limited by the mass of the plunger. The operation of a differential pump of electromagnetic action and the design of a vibrating pump are described. The description of constructive structures of working bodies of the differential pump of electromagnetic action is presented. The characteristics of the differential pump indicate the kinematic parameters on which the maximum frequency of the working body depends. The article describes in detail the interaction between the working body and the solenoid of the differential pump. The influence of mass on the working bodies, the influence of geometric features on the mass of the plunger, and the frequency of translational motion are stated. The characteristics of working bodies made of different materials are presented and described in detail. This generally made it possible to analyse the design of the plunger of the differential pump of electromagnetic action. Due to the careful choice of material, as well as the design features of the working body of the differential pump its productivity is increased successfully.